EFFECT OF PROCESSING ON THE PHYSICO-CHEMICAL PARAMETERS AND PROXIMATE COMPOSITION OF QUALITY PROTEIN MAIZE FLOUR - HELEENA JATI* , SARITA MISHRA, SALONI CHAUHAN; ROJA GHOSH (The Journal of Research ANGRAU, 2024)
The purpose of the study (2022) is to compare QPM maize flour’s physico-chemical composition before and after processing. A bag of 12 kg of QPM of the Shaktiman-5 variety was purchased. The gathered maize grains were cleaned by sifting out any remaining foreign material and sick or damaged seeds. In case of processing, the remaining 10 kg of maize grains were split into four equal sets in duplicate. There were 2.5 kg of corn grains in each replica. One set was preserved as the control (in triplicate) out of the four sets (in triplicate) for the study. In case of processing, the other three sets (each in triplicate) were retained. Boiling, roasting, and processing with alkali were the processing techniques used.The highest percentage of moisture content was found in the QPM control samples (13.06%), followed by samples of boiled maize (8.21%), alkalitreated samples (4.80%), and samples that had been roasted (3.65%). In terms of fat, it was discovered that roasted samples (3.92%) had the highest concentration, followed by alkali-treated maize samples (3.40%), boiling samples (3.28%), and control samples (3.23%). Ash level was highest in roasted samples (1.25%), then boiling samples (1.24%), untreated samples (1.14%), and samples treated with alkali (0.93%). The control samples had the highest percentage of fibre content (3.87%), followed by samples of boiled maize (3.79%), alkali-treated samples (3.30%), and samples that had been roasted (2.64%). Alkali treated sample had the greatest protein content percentage (10.85%), followed by control maize. In terms of carbohydrates, roasted samples (77.77%), alkali-treated samples (76.72%), boiling samples (73.13%), and control samples (67.87%) showed the highest amount.While it dropped in alkali-treated maize samples (18.42%), the proportion of ash concentration increased in boiled (8.77%) and roasted (9.65%) samples. After processing the QPM of the Shaktiman-5 variety, there were unquestionably both qualitative and quantitative modifications.